PENGARUH KETERAMPILAN MENGAJAR GURU DAN KESIAPAN BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN (PKK) KELAS XI SMK GKPI 1 PEMATANG SIANTAR - Dody A Lumban Toruan; Binsar Tison Gultom; Debbi Petra Meyana Sitorus (JOURNAL SAINS STUDENT RESEARCH, 2024)
The problem in this research is the low PKK learning outcomes of students in the learning process. This research aims to determine the influence of teacher teaching skills and student learning readiness on student learning outcomes in class XI PKK subjects at SMK GKPI 1 Pematangsiantar The type of research used in this research is quantitative research with a research design using a survey design. The population in this study was all students in class XI of SMK GKPI 1 Pematangsiantar. The type of research used in this research was quantitative research with a research design using a survey design. The population in this study was all 171 class XI students at SMK GKPI 1 Pematangsiantar. The sample in this study was 120 students. The sampling technique uses the Random Sample sampling technique. Data collection techniques use observation, documentation, and questionnaires. Data were analyzed using normality test, linearity test, multicollinearism test, heteroscedasticity test, multiple regression analysis, t test, F test, and coefficient of determination test.The research results show that there is an influence of Teacher Teaching Skills on student learning outcomes with tcount (3.813) > table value (1.658). Furthermore, there is an influence of Student Learning Readiness on learning outcomes with tcount (1.792) > ttable value (1.658). And there is an influence of Teacher Teaching Skills and Learning Readiness on learning outcomes with Fcount (6.154) > Ftable value (2.68)